Suppression of NF‐κB‐induced chronic inflammation mitigates inflammatory osteolysis in the murine continuous polyethylene particle infusion model. Issue 10 (28th March 2021) - Utsunomiya, Takeshi; Zhang, Ning; Lin, Tzuhua; Kohno, Yusuke; Ueno, Masaya; Maruyama, Masahiro; Huang, Ejun; Rhee, Claire; Yao, Zhenyu; Goodman, Stuart B.
Abstract: Wear particle‐associated bone loss (periprosthetic osteolysis) constrains the longevity of total joint arthroplasty (TJA). Wear particles induce a prolonged upregulation of nuclear factor kappa B (NF‐κB) signaling in macrophages and osteoclasts. Synthetic double‐stranded oligodeoxynucleotides (ODNs) can prevent the binding of NF‐κB to the promoter regions of targeted genes and inhibit genetic activation. We tested the hypothesis that polyethylene‐particle induced chronic inflammatory bone loss could be suppressed by local delivery of NF‐κB decoy ODNs in murine in vivo model. Polyethylene particles were continuously infused into the medullary cavity of the distal femur for 6 weeks to induce chronic inflammation, and micro‐computational tomography and immunohistochemical analysis were performed. Particle‐induced chronic inflammation resulted in lower BMD values, an increase in osteoclastogenesis and nuclear translocation of p65, a prolonged M1 pro‐inflammatory macrophage phenotype, and a decrease of M2 anti‐inflammatory macrophage phenotype. Delayed timing of local infusion of NF‐κB decoy ODN for the last 3 weeks reversed polyethylene‐particle associated chronic inflammatory bone loss and facilitated bone healing. This study demonstrated that polyethylene‐particle associated chronic inflammatory osteolysis can be effectively modulated via interference with the NF‐κB pathway; this minimally invasive intervention could potentially be an efficacious therapeutic strategy for periprosthetic osteolysis after TJA.